How Does The Public Respond To The Impact Of Carbon Tax Implementation Planning In DKI Jakarta? - Aurel , Princes; Varga, Fatimah; Putri, Dina Rachma; Nafilaty, Najwa Laila; Diaz, Amanda Maheswari Fatima; Firmansyah, Amrie (Educoretax, 2024)
Implementing a carbon tax is a policy to overcome the impact of carbon emissions on the decline in environmental quality. Implementing carbon tax policies can have complex impacts in various fields, such as economic, environmental, social, and political. This research analyzes the public's open response to the impact of carbon tax implementation. The research uses a qualitative and S-O-R method to analyze the public's response to the carbon tax. Data collection methods are carried out through interviews, observation, and documentation. The criteria for selecting sources (informants) in this research are people in DKI Jakarta who have an NPWP (Tax ID number), owners, and users of motorized vehicles, as well as academics in the field of taxation. Data analysis was done in data reduction, display, and conclusion. The analysis results in this research show that most people respond to implementing the carbon tax by agreeing with income redistribution as a reduction in rates for other types of taxes. In the environmental aspect, there is a positive response to implementing a carbon tax in reducing the impact of carbon emissions. Various responses highlighted the principles of justice regarding social inequality between social groups and the need to evaluate policy instruments in socio-political aspects. Public approval for implementing a carbon tax considering economic changes and environmental awareness still underlines the need for a fairer socio-political approach.